THE ESSENCE AND FEATURES OF STATE REGULATION OF RURAL DEVELOPMENT (International Journal of Innovative Technologies in Economy, 2020)
The article substantiates the need for effective state regulation of rural development, since overcoming the crisis requires both the mobilization of significant resources and the introduction of effective regulatory methods. The functions of state regulation of rural development are outlined and the relationship with the problems of rural development identified. The main problems of the modern village from the point of view of sustainable development are considered, which takes into account the real unity and interaction of the basic structural elements of rural territories.It has been found that effective state regulation of rural development should be based on a system of principles that should take into account the specific features of rural areas as an object of state regulation. The directions of actions of the authorities within each principle are determined. It is substantiated that the effectiveness of regulation of rural development depends on the mechanisms of state influence on their development. The instruments, methods and methods of action of the state authorities in terms of each mechanism are considered. It is noted that the peculiarities of state regulation of rural development lay in the real unity of their basic structural elements: economic base, social and environmental spheres. Characteristics of such components of rural population as "quality of life" and "standard of living" are given, as well as terms used in the conceptual and conceptual field of quality of life research. The analysis of scientific works on the quality and standard of living of the population revealed the components that are most commonly used in its assessment at the regional level. The concept of "state regulation of rural development" is formulated. It is substantiated that the necessity of state regulation of rural territories implies the use of functional- territorial system of public administration, which will allow to ensure optimal interaction between public authorities and local self-government.